2022
DOI: 10.3390/ijms23073636
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to Lymphocyte Ratio: An Emerging Marker of the Relationships between the Immune System and Diseases

Abstract: Over the last 10 years, the evaluation of the neutrophil-to-lymphocyte ratio (NLR) as an emerging marker of diseases has become a compelling field of bio-medical research. Although a precise and unique cut-off value has not been yet found, its role as a flag of immune system homeostasis is well established. NLR has a well-known prognostic value and independently correlates with mortality in the general population and in several specific subsets of disease (sepsis, pneumonia, COVID-19, cancer, etc.). Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
187
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(304 citation statements)
references
References 62 publications
7
187
1
2
Order By: Relevance
“…Other studies, considerably smaller than ours, have also identified role of NLR in identification of severe disease. 26,27 Reviews have concluded that this is an important marker, 7,8,23,28 and the present study which is a larger than most of the previous studies, confirms this observation.…”
Section: Discussionsupporting
confidence: 85%
“…Other studies, considerably smaller than ours, have also identified role of NLR in identification of severe disease. 26,27 Reviews have concluded that this is an important marker, 7,8,23,28 and the present study which is a larger than most of the previous studies, confirms this observation.…”
Section: Discussionsupporting
confidence: 85%
“…M2-derived exosomes can circulate invasion-potentiating miRNAs in the peripheral blood and deliver them to cancer cells for promoted cancer cell growth and invasion, with one example being the delivery of miRNA-223 to breast cancer cells ( 42 ). Neutrophils play both tumor-promoting and tumoricidal functions in the innate immune system through the production of, e.g., cytokines and proteases ( 60 ). Neutrophil-derived exosomes convey tumor-promotive roles by loading these parental contents ( 43 ).…”
Section: Exosome For Onco-therapeuticsmentioning
confidence: 99%
“…The neutrophil-to-lymphocyte ratio (NLR) is the number of neutrophils divided by the number of lymphocytes measured in peripheral blood. The clinical value of NLR has been extensively studied and considered as a reliable and emerging predictor reflecting the relationship the immune system and diseases [ 6 ]. The attractive characteristics of NLR is that it can be rapidly obtained and calculated from peripheral blood, and the value can reflect the status of innate immunity and adaptive immunity through neutrophils and lymphocytes, respectively.…”
Section: Introductionmentioning
confidence: 99%